Olefin metathesis for site-selective protein modification - Lin, YA (2013)
Site-selective protein modification has become an important tool to study protein functions in chemical biology. In the preliminary work, allyl sulfides were found to be reactive substrates in aqueous cross-metathesis (CM) enabling the first examples of protein modification via this approach. In order to access the enhanced CM reactivity of allyl sulfide on proteins, facile chemical methods to install S-allyl cysteine on protein surface were developed. In particular, a cysteine-specific allylating reagent – allyl selenocyanate was used on protein substrate for the first time. The substrate scope of allyl sulfide-tagged proteins and factors that affect the outcome of CM was also investigated. A range of metathesis substrates containing different olefin tether of various lengths were screened; allyl ethers were found to be most suitable as CM partners. By reducing the steric hindrance around the allyl sulfide on protein surface through a chemical spacer, the rate and conversion of metathesis reaction on proteins was greatly enhanced. Moreover, allyl selenides were found to be more reactive than allyl sulfides in CM and enabled reactions with substrates that were previously impossible for the corresponding sulfur-analogue. Through this work, substrate selection guidelines for successful metathesis reaction on proteins were established. Rapid Se-relayed CM was further investigated through biomimetic chemical access to Se-allyl selenocysteine (Seac) via dehydroalanine. On-protein reaction kinetics revealed rate constants of Seac-mediated CM to be comparable or superior to off-protein rates of many current bioconjugations. This CM strategy was applied to histone proteins to install a mimic of acetylated lysine (K9Ac, an epigenetic marker). The resulting synthetic H3 was successfully recognized by antibody that binds natural H3-K9Ac. A Cope-type selenoxide elimination subsequently allowed the removal of such modification to regenerate dehydroalanine. Finally, preliminary research efforts towards metabolic incorporation of allyl sulfide-containing amino acid into proteins, and CM on cell surfaces were discussed.